Harmonized benchmark labels of the hippocampus on magnetic resonance: The EADC‐ADNI project. Issue 2 (14th September 2014) - Bocchetta, Martina; Boccardi, Marina; Ganzola, Rossana; Apostolova, Liana G.; Preboske, Gregory; Wolf, Dominik; Ferrari, Clarissa; Pasqualetti, Patrizio; Robitaille, Nicolas; Duchesne, Simon; Jack, Clifford R.; Frisoni, Giovanni B.; et al.
Abstract: Background: A globally harmonized protocol (HarP) for manual hippocampal segmentation based on magnetic resonance has been recently developed by a task force from European Alzheimer's Disease Consortium (EADC) and Alzheimer's Disease Neuroimaging Initiative (ADNI). Our aim was to produce benchmark labels based on the HarP for manual segmentation. Methods: Five experts of manual hippocampal segmentation underwent specific training on the HarP and segmented 40 right and left hippocampi from 10 ADNI subjects on both 1.5 T and 3 T scans. An independent expert visually checked segmentations for compliance with the HarP. Descriptive measures of agreement between tracers were intraclass correlation coefficients (ICCs) of crude volumes and similarity coefficients of three‐dimensional volumes. Results: Two hundred labels have been provided for the 20 magnetic resonance images. Intra‐ and interrater ICCs were >0.94, and mean similarity coefficients were 1.5 T, 0.73 (95% confidence interval [CI], 0.71–0.75); 3 T, 0.75 (95% CI, 0.74–0.76). Conclusion: Certified benchmark labels have been produced based on the HarP to be used for tracers' training and qualification.